Ecomodernist tropes in Singapore science fiction - Uy, Jamie (Nanyang Technological University, 2023)
This thesis centers Singapore science fiction as a vital site for understanding ecomodernism not only as a practice of environmental governance but as a futuristic, techno-utopian aesthetic seamlessly hybridizing natural and industrial motifs. While ecomodernism is commonly understood as a school of thought advocating for the compatibility of capitalism with ecological conservation, this thesis argues that ecomodernism should also be understood as a collection of visual and narrative forms that idealize intensified industrialization as a means to solve climate change. As an island nation that advertises itself as a high-tech verdant utopia and global sustainability hub, Singapore is a pioneer of ecomodernism both in terms of policymaking and artistic style. Even before ecomodernism entered the popular lexicon with the publication of An Ecomodernist Manifesto in 2015, Singapore arguably practiced a similar approach since its Garden City mission launched in 1967, which involved several state-wide programs that positioned greening and economic growth as mutually beneficial. Singapore is a progenitor and paradigm of ecomodernism.